Asuhan Keperawatan pada Pasien Diabetes Melitus Tipe 2 dengan Masalah Keperawatan Ketidakstabilan Kadar Glukosa Darah Menggunakan Teknik Brisk Walking - Esti Winarni; Dewi Damayanti; Anton Surya Prasetya (Penerbit Goodwood, 2023)
Purpose: Diabetes mellitus can be characterized by chronic metabolic disorders due to the pancreas not being able to produce enough insulin or insulin cannot work effectively. One treatment to control blood glucose levels in people with diabetes mellitus is by doing aerobic exercise such as Brisk Walking. The aim of this study was to determine and analyze the application of the Brisk Walking technique intervention in overcoming the instability of blood glucose levels in type 2 diabetes mellitus patients in Puskesmas Gedong Air Bandar Lampung. Methodology: The method in this application is an applied method or applied research with a pretest and posttest research design with a population of 2 respondents. The instrument in this study uses the Brisk Walking standard operating procedure (SOP) guidelines and a blood glucose level measurement tool in the form of a glucometer. Results: The results of this study indicate that before and after the application of the Brisk Walking technique was given to both respondents they were able to overcome the instability of blood glucose levels with an average value of a decrease in the first respondent of 32.67 mg / dl and the second respondent of 24 mg / dl. The conclusion of this study is that the application of the Brisk Walking technique given has a positive impact on clients with type 2 diabetes mellitus in overcoming the instability of blood glucose levels.